Glycaemic control, lipid profile, blood pressure and body weight status among diabetics in rural Malaysia. - Abu Saad, Hazizi; Yassin, Zaitun; Kandiah, Mirnalini; Chan, S.P. (Japan International Cultural Exchange Foundation, 2009)
Diabetes is associated with a high risk of cardiovascular disease. The management of blood glucose, dyslipidaemia and other modifiable risk factor, is a key element in the multifactorial approach to prevent complications of type 2 diabetes.